PENERAPAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII - jimi ajijan; Eli Syarifah Aeni; Riana Dwi Lestari (IKIP Siliwangi, 2023)
Learning to write the text of the observation report is studied at the junior secondary level which conveys observations of an object in the form of a general description of the object being observed and studied. However, learning activities to write the text of the observation report are still lacking so that learning innovation is needed through the liveworksheet application. One of them uses a discovery learning model assisted by the liveworksheet application. The purpose of this study is to find out the pre-test and post-test of student learning outcomes in writing observation texts using the discovery learning method assisted by the liveworksheet application. The research method used is a quantitative method of experimentation with data collection techniques in the form of pre-test scores and post-test scores. The research project was 31 students of SMPN 01 Gununghalu. Based on the results of the study, a normal distributed value was obtained and with an average prestest value of 69.83 and an average postest value of 80. With the increase in the average results in the pretest and posttest, it was concluded that in this study there was a positive influence on the application of the discovery learning model on learning to write the text of the observation report.